MOTIVASI, DISIPLIN DAN KOMPETENSI SDM MENINGKATKAN KINERJA TENAGA AHLI DPR-RI FRAKSI GOLKAR - Irtanto, Bobby; Sembiring, Edison C.; Jamalulail (Universitas Bina Taruna Gorontalo, 2025)
The research aims to examine the influence of human resource quality, work motivation, and work discipline on the performance of expert members of the House of Representatives of the Republic of Indonesia. This type of research is a quantitative research with a research location in the secretariat building of the House of Representatives office, which was carried out from November 2023 to June 2024. The sample was determined using the Slovin formula, resulting in 51 randomly selected people. Data analysis uses the Structural Equation Model (SEM) which uses the SmartPLS 4.0 application. The results showed that work motivation did not have a significant effect on performance, while HR discipline and competence had a positive influence. Work discipline plays an important role in improving performance, and competence provides sufficient influence. The suggestions of this research include improving discipline, competence, and attention to the welfare of experts through adjustments to working hours. Further research is needed to deepen these findings for wider benefits.